DETERMINANTS OF SOCIALIZATION PATTERNS IN UNITED ARAB EMIRATES FAMILY CASE STUDY: STUDENTS AT UNIVERSITY OF SHARJAH - Wafa Barhoumi; Fatima Algharbawi; Hussein Alothman (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The study aimed to identify the demographic determinants that control the various patterns of "authoritarian, tolerant and democratic" socialization by focusing on three basic dimensions, first: What are the patterns of social upbringing at the University of Sharjah? Second: According to these patterns, what is the most common pattern of socialization in the Emirati family in Sharjah? Third: Do the patterns of socialization in Sharjah differ according to the demographic, social and economic characteristics of the parents and the respondents? The study found that the most common pattern of socialization among students of the University of Sharjah is the authoritarian pattern. Accordingly, the prevailing pattern in the Emirati family is the authoritarian style, which is characterized by strictness and imposition of opinion, which may be due to the nature of the patriarchal society, which is still governed by customs, traditions, and the semi-extended family. The results showed the effect of the parents’ economic and social determinants such as "work status, family size, parental education, and economic status" on the patterns of socialization, as they stimulate and support the results of a study on the prevalence and dominance of the authoritarian style in the Emirati family.